The protective role of Pomegranate seed oil (Pometone) on serum protein in sodium fluoride treated female rats: Ellaf Hussian Ali and Baraa Najim Al-Okaily - Al-Okaily, Baraa Najim (The Iraqi Journal of Veterinary Medicine, 2016)
This study is designed to determin the protective role of pomegranate seed oil against deleterious effect induced by sodium fluoride on serum proteins in rats. Forty (40) adult female rats were randomly divided into four equal group (10/group) and treated daily for 40 days as following: Group C administered distilled water (control), group T1 received sodium fluoride 120 ppm/liter in drinking water, group T2 received both sodium fluoride 120 ppm/liter in drinking water and Pometone 30 mg/kg B.w. orally and group T3 administered Pometone 30 mg/kg B.w. orally. Fasting blood samples were collected at 0, 20 and 40 days of the experimental periods and serum samples were aliquoted for estimation serum total protein, albumin and globulin concentrations. Also, protein electrophoresis was measured. The results revealed that sodium fluoride caused significant reduction in serum total protein, albumin and globulin concentrations, in addition to changes in the patterns of serum protein fractions % (albumin, α1-globulin, α2-globulin, β-globulin and γ-globulin) as compared with control rats. In conclusion Pomegranate seed oil caused elevation of proteins concentration as compared to group T1 and could potentially be beneficial in preventing the hepatic damage caused by sodium fluoride.